Odpowiedź :
Odpowiedź:
a. [tex]= -(7-3\frac{3}{7} )=-(6\frac{7}{7} -3\frac{3}{7} ) =-3\frac{4}{7}[/tex]
b. -5,4 + 6 = 6 - 5,4 = 0,6
c. [tex]= -(\frac{3}{9} +1\frac{1}{9} ) =-1\frac{4}{9}[/tex]
d. [tex]1\frac{8}{18} -3\frac{15}{18} =-(3\frac{15}{18}-1\frac{8}{18} )=-2\frac{7}{18 }[/tex]
e. [tex]= -7 \frac{1}{5} + 3\frac{4}{7} =-(7\frac{1}{5} -3\frac{4}{7} )=-(7\frac{7}{35} -3\frac{20}{35} )= - (6\frac{42}{35} -3\frac{20}{35} )=-3\frac{22}{35}[/tex]
f. [tex]=-2\frac{1}{7} +5\frac{3}{4} = 5\frac{3}{4} -2\frac{1}{7} =5\frac{21}{28} - 2\frac{4}{28} = 3\frac{17}{28}[/tex]
g.[tex]=(3\frac{1}{7} + 2\frac{3}{4} ) = -(3\frac{4}{28} + 2\frac{21}{28} )=-5\frac{25}{28}[/tex]
h. [tex]=-2\frac{8}{24} - \frac{21}{24} = -(2\frac{8}{24} -\frac{21}{24})=-(1\frac{32}{24}-\frac{21}{24}) = -1\frac{11}{24}[/tex]
i. = -(1,3 - 0,7) = -0,6
j. = 5,1 - 2,4 = 2,7
k. -6 + 2,7 = - (6 - 2,7) = -3,3
l. = - (2,1 + 3,7) = -5,8
m. - 6,8 + 4,2 = -(6,8 - 4,2) = -2,6
n. = 4,75 - 2,25 = 2,5
o. = -1,2 + 2,1 = 2,1 - 1,2 = 0,9
p. = -(6,8 - 2,3) = -4,5
Szczegółowe wyjaśnienie: